2020
DOI: 10.1111/sms.13893
|View full text |Cite
|
Sign up to set email alerts
|

The associations between meeting 24‐hour movement guidelines and adiposity in Asian Adolescents: The Asia‐Fit Study

Abstract: Background: To prevent adolescent obesity, recent research suggests that physical activity (PA), recreational screen-time, and sleep duration are codependent behaviours that being in a movement behaviour continuum in a 24-hour period. Yet, it is unknown about compliance with the 24-hour movement guidelines in Asian adolescents, and how these movement behaviours collectively affect overweight and obesity in adolescents. The purposes of this study were to compare compliance with the 24-movement guidelines in Asi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 49 publications
(111 reference statements)
1
39
0
Order By: Relevance
“…Research evidence indicated that FMS in preschoolers was negatively related to their sedentary behavior (SB) [ 12 ], which mainly comprised screen time (ST). Therefore, the World Health Organization’s 24-Hour Movement Guidelines recommended that 3–4-year-old preschoolers should have limited recreational ST of no more than one hour per day, and 5-year-olds should have no more than two hours per day [ 13 , 14 , 15 ]. It is also known that adequate sleep plays a fundamental role in the memory consolidation process and in the acquisition and retention of information [ 16 ]; thus, researchers postulated that inadequate sleep is negatively correlated with FMS acquisition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence indicated that FMS in preschoolers was negatively related to their sedentary behavior (SB) [ 12 ], which mainly comprised screen time (ST). Therefore, the World Health Organization’s 24-Hour Movement Guidelines recommended that 3–4-year-old preschoolers should have limited recreational ST of no more than one hour per day, and 5-year-olds should have no more than two hours per day [ 13 , 14 , 15 ]. It is also known that adequate sleep plays a fundamental role in the memory consolidation process and in the acquisition and retention of information [ 16 ]; thus, researchers postulated that inadequate sleep is negatively correlated with FMS acquisition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence supporting the beneficial effects of meeting these 24 h movement guidelines on obesity has been equivocal. For instance, a cross-sectional study showed no association between meeting all 24 h movement recommendations and adiposity indicators [ 38 ], another study reported a negative association between the number of guidelines met and adolescents’ body composition [ 39 ] and a multi-national study observed within and between-country variations in the recommended movement behaviors among participants [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence demonstrated that regular physical activity (PA) (especially with moderate-to-vigorous intensity), limited screen time (ST) and proper sleep duration with good quality, collectively referred to as 24 h movement behaviors, are crucial modifiable correlates of weight status (i.e., overweight/obese or not, as identified by body mass index, BMI) and body composition (e.g., PBF, FFM, SMM) in children and adolescents [ 2 , 9 , 10 ]. For instance, engaging in a larger amount of PA (especially with high intensity) was found be significantly associated with a lower risk of overweight/obesity, lower levels of PBF and higher levels of FFM and SMM in children from different countries [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%